Survailen Aktif Infectious Myonecrosis Virus (Imnv) pada Udang Vannamei (Litopenaeus vannamei) yang Dibudidayakan di Jawa Timur Dan Bali - Yani Lestari Nur’aini; Bambang Hanggono; Slamet Subyakto; Gemi Triastutik (Jurnal Perikanan Universitas Gadjah Mada, 2007)
An active surveillance of infectious myonecrosis virus (IMNV) in pond-cultured white shrimp (Litopenaeus vannamei) was conducted to determine the status of this disease. Samples of white shrimp (L. vannamei) were taken from ponds in East Java and Bali using proportional sampling. The sample was subjected to IMNV detection with Polymerase Chain Reaction (PCR) method and confirmed with histopathology. Results of this study showed that IMNV was found in shrimp samples from Kapongan, Situbondo district with the prevalence of 11,1%. Meanwhile, samples from other districts in East Java and Bali had no IMNV disease during this study. There is no treatment for viral disease in shrimp culture. Therefore, control of movement of live shrimp and application of biosecurity-area based should be more implemented among the shrimp culture area.